Pengaruh Layout dan Desain Interior terhadap Kepuasan Pelanggan di Muso Art Café Batam - Clarissa, Tiffany; Ilham, Wahyudi; Alhamdi, Rezki; Dailami, Dailami (Publikasi Indonesia, 2025)
Batam City is one of the most popular tourist destinations. With the increasing demand for tourism in Batam City, various types of tourism-supporting businesses have emerged, particularly in the Food and Beverage sector. Many F&B businesses focus not only on the quality of their food but also on enhancing the experience of their guests, one of which is by optimmalizing the atmosphere through the applied layout and interior design. This study was conducted to determine whether spatial layout and interior design influence the level of customer satisfaction at Muso Art Cafe. This study used a descriptive quantitative method through data collected through observation, interviews, and questionnaires. The required sample size was 119 respondents and was obtained through accidental. Based on data analysis, the research indicators are valid and reliable, and free from symptoms of multicollinearity. The R2 result is 0.594, indicating that 59.4% of customer satisfaction is influenced by layout and interior design. Based on the results of the T-Statistic test, spatial layout has a significant positive effect with a value of 5.541, which meets the criteria, of > 1.96. The same applies to interior design, where this variable has a significant positive effect with a value of 4.738. Based on these results, it can be concluded that spatial layout and interior design have a simultaneous and partial effect on customer satisfaction. This proves that layout and interior design is something important that must be well-excecuted by the business owners especially in the F&B Industry.